Socio-demographic analysis of youth in the Caribbean - a three country case study (ECLAC Port of SpainTT, 2008)
Analyzes available and accessible census data ( 2000 census round) for three Eastern Caribbean countries with a focus on the situation of children, youth and young families.
Keywords: YOUTH